Synthesis and evaluations of novel photoinitiators with side-chain benzophenone, derived from alkyl α-hydroxymethacrylates - Karahan, Ozlem; Balta, Demet Karaca; Arsu, Nergis; Avci, Duygu (ELSEVIER SCIENCE SA, 2014)
A novel monomeric photoinitiator, tert-butyl 2-((4-benzoylphenoxy)methyl)acrylate (1), with a side-chain benzophenone (BP) group was synthesized from tert-butyl alpha-bromo methacrylate (TBBr) and 4-hyroxybenzophenone. It was thermally homo- and copolymerized with a coinitiator, N,N-dimethylaminoethyl methacrylate (DMAEM), using free radical polymerization to give the corresponding polymeric photoinitiators (poly-1 and poly(1-co-DMAEM)). The polymeric photoinitiators showed similar UV absorption spectra to 1, which were red-shifted compared to BP. Photophysical studies such as phosphorescence and laser flash photolysis in addition to photopolymerization of methacrylates were performed. The photopolymerizations of triethylene glycol dimethacrylate (TEGDMA) and 1,6-hexanedioldiacrylate (HDDA) initiated by 1, poly-1, poly(1-co-DMAEM) and BP were studied by photo-DSC. The polymeric initiator (poly-1) was found to have higher efficiency than BP and monomeric initiatior 1. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Photopolymerization; Polymeric photoinitiator; Benzophenone; Synthesis; Alkyl alpha-hydroxymethacrylates; FREE-RADICAL POLYMERIZATION; COINITIATOR AMINE; MAIN-CHAIN; MOIETIES; THIOXANTHONE; POLYMERS; STATE; Chemistry